Molten salt and method for producing molten salt

By mixing alkali metal salts with organic polymers to form supercooled molten salts, the problem of high melting point of alkali metal molten salts is solved, achieving a stable liquid state and high conductivity at room temperature, making it suitable as an electrolyte for lithium secondary batteries.

CN120814084APending Publication Date: 2025-10-17NAT UNIV CORP YOKOHAMA NAT UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202480016447.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-06
Filing Date
2024-02-15
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing alkali metal molten salts have high melting points, limiting their use at high temperatures. Furthermore, existing mixed salts have high glass transition temperatures in the room temperature range, making it difficult to maintain a liquid state at room temperature.

Method used

By mixing alkali metal salts with specific organic polymers, a supercooled molten salt is formed. The specific method includes a dissolution process and a decompression process. The organic polymers are used to lower the glass transition temperature, so that the salt remains in a liquid state at room temperature.

Benefits of technology

A molten salt with a low glass transition temperature has been achieved, which can stably maintain a liquid state at room temperature, improving the safety and conductivity of the molten salt, and making it suitable for use as an electrolyte in lithium secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120814084A_ABST
    Figure CN120814084A_ABST
Patent Text Reader

Abstract

Provided is a molten salt having a low glass transition temperature. A molten salt according to an embodiment includes an alkali metal salt having an anion having an amide structure or a methylate structure, or an anion selected from the group consisting of BF4, PF6, ClO4, CF3SO3, C2F5SO3, C4F9SO3, and CF3CO2, and 5 mol% to 50 mol% of an organic polymer, the alkali metal salt having an anion having an amide structure or a methylate structure, or an anion selected from the group consisting of BF4, PF6, ClO4, CF3SO3, C2F5SO3, C4F9SO3, and CF3CO2. The organic polymer is one or more kinds of polar functional groups of N, O and F coordinated with cations of the alkali metal salt, and the glass transition temperature of the organic polymer is lower than the glass transition temperature of the alkali metal salt simple substance.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] Embodiments of the present application relate to a molten salt and a method for producing a molten salt. BACKGROUND

[0002] Flammable organic solvents are used in electrolytes for lithium secondary batteries. In order to improve safety, electrolytes that are flame retardant are required.

[0003] Alkali metal molten salts exhibit flame retardancy and have low vapor pressure because they do not contain solvents. By using an alkali metal molten salt containing a lithium salt as an electrolyte, a lithium secondary battery with high safety can be provided. In addition, alkali metal molten salts do not generate concentration polarization, and thus have high mobility when used in a battery.

[0004] However, alkali metal molten salts have high melting points, and thus are limited to use at high temperatures as electrolytes.

[0005] Japanese Patent Application Publication No. 2014-165110 discloses a lithium secondary battery that operates in the room temperature region to 100°C or higher by using a mixed salt in which Li[(SO2)(CF3SO2)N] and Li[(FSO2)N] are mixed.

[0006] Japanese Patent Application Publication No. 2013-232327 discloses a molten salt battery having an electrolyte containing a mixture of Na(FSA)-K(FSA).

[0007] International Publication No. 2006 / 057231 discloses a plating bath composed of a molten salt containing an organic high molecule.

[0008] The organic high molecule of the above-described plating bath is an additive for smoothing the surface of a plated film. Thus, the content of the organic high molecule is 0.0001 mass% or more and 1 mass% or less. PRIOR ART DOCUMENTS PATENT DOCUMENTS

[0009] Patent Document 1: Japanese Patent Application Publication No. 2014-165110 Patent Document 2: Japanese Patent Application Publication No. 2013-232327 Patent Document 3: International Publication No. 2006 / 057231 SUMMARY PROBLEMS TO BE SOLVED BY THE INVENTION

[0010] An object of embodiments of the present application is to provide a molten salt and a method for producing a molten salt. MEANS FOR SOLVING THE PROBLEMS

[0011] The molten salt of an embodiment of the present invention comprises an alkali metal salt and 5 mol % or more of an organic polymer, wherein the alkali metal salt comprises an anion having an amide structure or a methylate structure, or an anion selected from BF4, PF6, ClO4, CF3SO3, C2F5SO3, C4F9SO3, and CF3CO2, and the organic polymer is one or more polar functional groups having N, O, or F coordinated with the cation of the alkali metal salt, and the glass transition temperature is lower than the glass transition temperature of the alkali metal salt monomer.

[0012] Another embodiment of the method for producing a molten salt comprises: a dissolution step, in which an alkali metal salt including an anion having an amide structure or a methylate structure, or an anion selected from BF4, PF6, ClO4, CF3SO3, C2F5SO3, C4F9SO3, and CF3CO2, and one or more organic polymers having polar functional groups of N, O, and F coordinated to the cations of the alkali metal salt in an amount of 5 mol% or more and 50 mol% or less relative to the alkali metal salt are dissolved in an organic solvent; and a decompression step, in which the molten salt containing the organic solvent is decompressed to form a supercooled state. Effects of the Invention

[0013] According to the embodiments of the present invention, a molten salt having a low glass transition temperature and a method for producing a molten salt having a low glass transition temperature can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a graph showing the glass transition temperatures of molten salts containing PPC or PC. Figure 2 This is a diagram showing the range of the supercooled state of the molten salt according to the embodiment. Figure 3 This is a graph showing the electrodeposition state of the molten salt according to the embodiment. Figure 4 This is a graph showing the glass transition temperature of the molten salt according to the embodiment. Figure 5 This is a graph showing the liquid state maintenance time of the molten salt. Figure 6 This is a graph showing the relationship between the glass transition temperature and the liquid state maintenance time of the organic polymer of the molten salt according to the embodiment. Figure 7 This is a graph showing the relationship between the glass transition temperature of the molten salt and the glass transition temperature of the polymer according to the embodiment. DETAILED DESCRIPTION

[0015] <Implementation Method> The molten salt of the embodiment of the present application contains an alkali metal salt and an organic polymer. Specifically, the molten salt contains Li(FTA) (lithium fluorosulfonyl(trifluoromethylsulfonyl)amide salt) as an amide lithium salt and PPC (polypropylene carbonate) as an organic polymer. The number average molecular weight Mn of the PPC is 50,000 or less.

[0016] Note that the amide lithium salt is sometimes also referred to as an imide lithium salt by those skilled in the art. For example, Li(FTA) (lithium fluorosulfonyl(trifluoromethylsulfonyl)amide salt) is also referred to as LiFTI (lithium fluorosulfonyl(trifluoromethylsulfonyl)imide salt). Li(FTA) and LiFTI refer to the same lithium salt.

[0017] The following molten salts were each produced by a dissolving process of dissolving a mixture of Li(FTA) and PPC in AN (acetonitrile) as an organic solvent and a reduced pressure process of removing the organic solvent by subjecting the dissolved solution to reduced pressure.

[0018] In the dissolving process, Li(FTA) and PPC were mixed in the following proportions, the mixture was dissolved in acetonitrile, and the dissolved solution was left to stand at 45°C for 1 day.

[0019] PPC (100 mol%) Li(FTA) : PPC = 10 mol% : 90 mol% Li(FTA) : PPC = 30 mol% : 70 mol% Li(FTA) : PPC = 50 mol% : 50 mol% Li(FTA) : PPC = 70 mol% : 30 mol% Li(FTA) : PPC = 90 mol% : 10 mol% Li(FTA) (100 mol%)

[0020] In the reduced pressure process, the dissolved solution was left to stand at 65°C for 1 day, and then vacuum dried at 105°C for about 2 hours, and after the acetonitrile was removed, cooled to room temperature (25°C), whereby a molten salt in a supercooled state was produced.

[0021] The melting point Tm of Li(FTA) is about 100°C, but Li(FTA) containing PPC produced by the above method becomes a deeply supercooled salt that is in a liquid state at room temperature below the melting point. Supercooling refers to a state in which a substance is in a liquid state even below the melting point in a phase transition of the substance.

[0022] Figure 1The relationship between the composition of the molten salt and the glass transition temperature Tg is shown. The glass transition temperature Tg of the supercooled molten salt was measured using a differential scanning calorimeter (DSC) at 5°C / min from -150°C to 150°C. The glass transition temperature Tg of the supercooled molten salt was measured from the baseline shift of the DSC curve (refer to Figure 2 ). For comparison, instead of PPC, the glass transition temperature Tg was also measured for a molten salt to which PC (propylene carbonate) was added as a monomer.

[0023] As shown in Figure 2 , the molten salt not containing PPC (Li(FTA) monomer) is accompanied by a large heat generation (ΔQ) at the melting point. The melting point peak of the Li(FTA) molten salt containing PC disappears, and the glass transition temperature Tg accompanying crystallization changes approximately linearly according to the composition between the Tg of Li(FTA) (about 0°C) and the Tg of PC (about -120°C) as in the well-known Gordon-Taylor equation.

[0024] On the other hand, the glass transition temperature Tg of the Li(FTA) molten salt containing PPC is lower than the Tg of Li(FTA) (about 0°C) and the glass transition temperature Tg of PPC (10°C to 35°C). In particular, the glass transition temperature Tg of the molten salt in which Li(FTA) is 50 mol% to 90 mol% decreases to -30°C or less. The change in the glass transition temperature Tg of the molten salt of the embodiment is an abnormal behavior that cannot be predicted according to the well-known theory, and is caused by the supercooling phenomenon. That is, unlike the decrease in the melting point (solidification temperature) in a general mixed salt, the glass transition temperature Tg decreases in the molten salt of the present embodiment.

[0025] As shown in the differential thermal analysis results of Figure 2 , the molten salt containing PPC becomes a supercooled state due to the decrease in the glass transition temperature Tg, and is in an amorphous state that is liquid over a wide range of room temperature (25°C) or less.

[0026] For example, in the case of visually confirming the molten salt of 90 mol% Li(FTA) - 10 mol% PPC, the liquid state is maintained at room temperature for one month or more. On the other hand, the molten salt of 90 mol% Li(FTA) - 10 mol% PC solidifies (crystallizes) in a short time.

[0027] That is, the organic substance added to Li(FTA) is a high molecule, which is the main reason for the decrease in the glass transition temperature Tg, and is necessary in order to obtain a supercooled molten salt in which the high molecule is stably added.

[0028] Note that if PPC is added, the glass transition temperature Tg of the molten salt decreases, but in order to stably maintain the liquid state, the amount of PPC added is preferably 5 mol% or more and 50 mol% or less.

[0029] The PPC is a non-conductor, and therefore, in the case where it is necessary to ensure the electrical conductivity of the molten salt, the amount of PPC added is preferably 20 mol% or less, and particularly preferably 15 mol% or less.

[0030] The temperature dependence of the electrical conductivity of 90 mol% Li(FTA) - 10 mol% PPC and Li(FTA) is shown in Table 1 below.

[0031]

[0032] The electrical conductivity of the supercooled molten salt near room temperature is lower than that of Li(FTA) exceeding the melting point. However, the supercooled molten salt also stably exhibits electrical conductivity near room temperature.

[0033] Next, using 90 mol% Li(FTA) - 10 mol% PPC, potentiostatic electrodeposition of Li metal to a Li plate (120°C) was performed, and the transference number was measured. Almost no concentration polarization was observed, and a value (0.94) equivalent to the transference number of the molten salt Li(FTA) already reported was calculated.

[0034] In addition, according to Cole-Cole plot analysis obtained by performing an alternating current impedance method, it was determined that the interfacial resistance was small.

[0035] Next, Li(FTA) molten salts to which 10 mol% of various organic polymers shown below were added were produced by a method similar to that of the Li(FTA) molten salt to which PPC was added, and the glass transition temperature Tg and stability were investigated. Among these, the organic solvent (solvent) used in the production was acetonitrile, acetone, or THF, and acetonitrile, which is easy to remove, was most preferable.

[0036] Polypropylene glycol (PPG): Mn = 2000 Polyethylene glycol (PEG, PEO): Mn = 35000 Polymethyl methacrylate (PMMA): Mn = 48000

[0037] As shown in Table 2, the Li(FTA) molten salt to which the above organic polymer was added exhibited abnormal lowering of the glass transition temperature Tg. That is, the glass transition temperature Tg of the molten salt to which the above organic polymer was added was lower than that of the alkali metal salt simple substance (Li(FTA)). Figure 4

[0038] Then, as shown in Table 3, the Li(FTA) molten salt to which the above organic polymer was added exhibited abnormal lowering of the glass transition temperature Tg. That is, the glass transition temperature Tg of the molten salt to which the above organic polymer was added was lower than that of the alkali metal salt simple substance (Li(FTA)). Figure 5 ​As shown in Table 1, the Li(FTA) molten salt to which each of the above-mentioned organic polymers was added maintained a liquid state for more than one week. In particular, the Li(FTA) molten salt to which PPC or PMMA was added maintained a liquid state for at least one month. In addition, the Li(FTA) molten salt to which PMMA was added maintained a liquid state even after several months.

[0039] Note that the upper limit / lower limit of the amount of each of the above-mentioned organic polymers added to the Li(FTA) is substantially the same as the upper limit / lower limit of the amount of PPC added. In addition, in order to maintain a stable supercooled state, the molecular weight Mn of the organic polymer is preferably 1,000 or more and 75,000 or less. In addition, the molten salt can contain a plurality of each of the above-mentioned organic polymers. That is, the molten salt can contain one or more of each of the above-mentioned organic polymers.

[0040] The supercooled-state organic polymer-added molten salt is expected to be used as an electrolyte for a battery. The supercooled molten salt solidifies after a long period of time. When the molten salt solidifies, the electrical conductivity sharply decreases. However, the solidified molten salt becomes a liquid state by heating to a temperature above the melting point of Li(FTA), and becomes a supercooled state again when the temperature decreases to below the melting point.

[0041] On the contrary, based on the electrical characteristics of the supercooled molten salt in which the electrical conductivity sharply increases with the passage of time, the supercooled molten salt is expected to be applied to a switch or the like that cuts off an electric current with the passage of time. In addition, the physical characteristics of the supercooled molten salt in which solidification occurs with the passage of time are also expected to be applied to various applications.

[0042] The alkali metal salt of the organic polymer-added molten salt of the present application contains an anion having an amide structure or a methide structure, or an anion selected from the group consisting of BF4, PF6, CIO4, CF3SO3, C2F5SO3, C4F9SO3, and CF3CO2. Specifically, as the alkali metal salt, a fluorine-containing amide lithium salt, a fluorine-containing methide lithium salt can be used.

[0043] The alkali metal salt is particularly preferably a fluorine-containing amide lithium salt (LiN(SO2(CF2)xF)(SO2(CF2)yF) (wherein x and y each independently represent an integer of 0 to 5). As the fluorine-containing amide lithium salt, for example, lithium bis(fluorosulfonyl)amide (Li(FSA)), lithium bis(trifluoromethanesulfonyl)amide (LiTFSA), lithium bis(pentafluoroethanesulfonyl)amide (LiBETA) can be listed.

[0044] In addition, the organic polymer used in the organic polymer-added molten salt of the present application has a polar functional group of N, O, or F coordinated with the cation of the alkali metal salt. Specifically, as the organic polymer, polypropylene glycol, polymethyl methacrylate, polyethylene glycol, polypropylene carbonate can be used.

[0045] The organic polymer additive molten salt of the present application is particularly preferably Li(FTA) and the organic polymer is particularly preferably polypropylene carbonate or polymethyl methacrylate, because the supercooling state is stable.

[0046] Note that a plurality of alkali metal salts can be used in combination as the alkali metal salt. That is, one or more of a plurality of alkali metal salts can be used as the alkali metal salt. The mixing ratio of the plurality of alkali metal salts can be appropriately selected. In order to effectively utilize the characteristics of each of the plurality of alkali metal salts, in the case where two salts A and B are mixed, A / B (mole %) is preferably (30 / 70) to (70 / 30).

[0047] Particularly, Li(FTA / FSA) mixed salt has high conductivity, and is therefore preferably used as the alkali metal salt of the present application. In addition, in Li[(FTA)x(FSA)y]-10 mole % PMMA mixed salt, the glass transition temperature Tg is lowest when X is 33 mole % to 55 mole %. As the organic polymer of the present application, polyvinylpyrrolidone (PVP) is also preferably used. Hereinafter, PVP having a molecular weight Mn of 40,000 is used.

[0048] As already explained, in order to stably maintain the liquid state, the amount of the organic polymer to be added is preferably 5 mole % or more and 50 mole % or less. Since the organic polymer is a non-conductor, in the case where it is necessary to ensure the conductivity of the molten salt, the amount of the organic polymer to be added is preferably 20 mole % or less, and particularly preferably 15 mole % or less.

[0049] The method for producing PVP additive molten salt is substantially the same as the method for producing the organic polymer additive molten salt already explained. In addition, although not shown, the glass transition temperature of the molten salt to which PVP is added is lower than the glass transition temperature of the alkali metal salt as a single substance.

[0050] Table 2 shows the temperature dependence of the conductivity of Li[(FTA) 0.5 (FSA) 0.5 ], 90 mole % Li[(FTA 0.5 (FSA) 0.5 ] / 10 mole % PMMA, and 90 mole % Li[(FTA 0.5 (FSA) 0.5 ] / 10 mole % PVP.

[0051]

[0052] Compared with Table 1, the conductivity of the organic high-molecular-added molten salt using Li(FTA / FSA) mixed salt is much higher than that of the organic high-molecular-added molten salt using Li(FTA). Therefore, the organic high-molecular-added molten salt using Li(FTA / FSA) mixed salt can be preferably used as an electrolyte of a battery compared with the organic high-molecular-added molten salt using Li(FTA).

[0053] Figure 6 is a graph showing the relationship between the liquid state maintenance time of various organic high-molecular-added molten salts A to G and the glass transition temperature of the organic high-molecule.

[0054] A: 90 mol% Li[(FTA) 0.5 (FSA) 0.5 ] / 10 mol% PVP B: 90 mol% Li[(FTA) 0.5 (FSA) 0.5 ] / 10 mol% PMMA C: 90 mol% Li(FTA) / 10 mol% PMMA D: 90 mol% Li(FTA) / 10 mol% PPC E: 90 mol% Li(FTA) / 10 mol% PEO F: 90 mol% Li(FTA) / 10 mol% PPPG G: 90 mol% Li(FTA) / 10 mol% PC

[0055] Further, Figure 6 the liquid state maintenance time shown is the time until a part of the liquid is crystallized, and in contrast to this, Figure 5 the liquid state maintenance time shown is the time until the entire liquid is crystallized.

[0056] In order to increase the conductivity of the molten salt, the carrier density of the alkali metal salt ion is preferably high. Therefore, the organic high-molecule preferably has a structure that promotes dissociation by weakening the interaction of the alkali metal ion and the counter anion and coordinating with the alkali metal ion.

[0057] Therefore, the added organic high-molecule is preferably a structure having one or more polar functions of N, O, F that coordinate with the cation of the alkali metal salt. Specifically, the polar function is an ester group, a carbonyl group, a cyano group, an imide group, an amino group, or a functional group having an ionic site.

[0058] In addition, it is suggested that the superplasticizing effect is large when adding an organic polymer with a high glass transition temperature. Therefore, it is preferred to have an organic polymer with a structure including a side chain group with a large rotation barrier. In addition, the more heterogeneous the system, the more likely it is to stably maintain a supercooled state, so an organic polymer with a wide molecular weight distribution is preferred.

[0059] Figure 7 The relationship between the glass transition temperature of the added organic polymer and the glass transition temperature of the molten salt (DSS) is shown.

[0060] PPC:Li[(FTA) 0.5 (FSA) 0.5 ] / PPC PBMA(poly(butyl methacrylate):Li[(FTA) 0.5 (FSA) 0.5 ] / PBMA PEMA(poly(ethyl methacrylate):Li[(FTA) 0.5 (FSA) 0.5 ] / PEMA PMMA:Li[(FTA) 0.5 (FSA) 0.5 ] / PMMA PVP:Li[(FTA) 0.5 (FSA) 0.5 ] / PVP

[0061] The molten salt to which an organic polymer having a glass transition temperature Tg higher than that of the alkali metal salt of the base material is added, especially an organic polymer having a glass transition temperature Tg exceeding 100°C (for example, PMMA (Tg≈106°C), PVP (Tg≈152°C)) maintains a liquid state for a very long time and is stable in the supercooled state, and therefore can be particularly preferably used.

[0062] <Modification> The molten salt of the modified example described below is similar to the molten salt of the embodiment, and similarly, even after removing the organic solvent added for dissolution, it stably maintains a supercooled state (liquid state). Therefore, the description of the same structure as the molten salt of the embodiment is omitted below.

[0063] It should be noted that the molten salt is a supercooled liquid. Figure 2 The results were determined by the exothermic peak (ΔQ) in differential thermal analysis and visual observation.

[0064] In the molten salt of the present modification example, the alkali metal salt is a potassium amide salt or a sodium amide salt. That is, the molten salt contains K(FTA) (potassium fluorosulfonyl(trifluoromethylsulfonyl)amide salt) as a potassium salt or K[(FTA) (potassium fluorosulfonyl(trifluoromethylsulfonyl)amide salt) as a sodium salt.

[0065] For example, 70 mol% K(FTA) / 30 mol% PMMA and 90 mol% K[(FTA) 0.5 (FSA) 0.5 ] / 10 mol% PMMA are in a liquid state. That is, after dissolving the mixed salt in AN as an organic solvent, even if the AN is removed, the liquid state (supercooled state) is maintained for more than 1 week. In DSC analysis, the melting point peak of the K(FTA) salt disappears at 20 mol% - 30 mol% of PMMA, and the melting point peak of the 90 mol% K[(FTA) 0.5 (FSA)0 .5 ] salt disappears at less than 10 mol% of PMMA. Furthermore, at the same PMMA concentration, the glass transition temperature Tg of the K[(FTA) 0.5 (FSA) 0.5 ] salt is lower than that of K[(FTA)].

[0066] For example, 80 mol% Na(FSA) / 20 mol% PMMA and 70 mol% Na(FSA) / 30 mol% PMMA are in a liquid state. However, if the AN is removed, 80 mol% Na(FTA) / 20 mol% PMMA becomes a solid. That is, the Na-based salt is different from the Li-based salt and the K-based salt, and the FSA salt is more easily obtained in a stable supercooled state than the FTA salt. Note that 80 mol% Na[(FTA) 0.5 (FSA) 0.5 ] / 20 mol% PMMA and 70 mol% Na[(FTA) 0.5 (FSA) 0.5 ] / 30 mol% PMMA are in a liquid state.

[0067] Table 3 shows the temperature dependence of the electrical conductivity of the molten salt of the present modification example.

[0068]

[0069] Compared with the molten salt containing only K(FTA) as the alkali metal salt, the molten salt obtained by adding an equimolar amount of more flexible K(FSA) to K(FTA) is in a more stable supercooled state.

[0070] Note that the molten salt of the embodiments and the present modification example can contain a mixed salt of two or more selected from a lithium amide salt, a potassium amide salt, and a sodium amide salt as the alkali metal salt.

[0071] The present application is not limited to the above-described embodiments and the like. Various changes, modifications, combinations of constituent elements, and the like can be made within the scope of the present application without changing the spirit of the present application.

Claims

1. A molten salt, characterized in that The molten salt contains an alkali metal salt and 5 mol% or more of an organic polymer, The alkali metal salt comprises an anion having an amide structure or a methide structure, or an anion selected from BF4, PF6, ClO4, CF3SO3, C2F5SO3, C4F9SO3 and CF3CO2, The organic polymer has one or more polar functional groups of N, O, and F coordinated with the cation of the alkali metal salt. The glass transition temperature of the molten salt is lower than the glass transition temperature of the alkali metal salt.

2. The molten salt according to claim 1, characterized in that The alkali metal salt is one or more selected from amide lithium salt, amide potassium salt or amide sodium salt, The organic polymer is one or more of polypropylene glycol, polyethylene glycol, polypropylene carbonate, polymethyl methacrylate, and polyvinyl pyrrolidone.

3. The molten salt according to claim 1, characterized in that The alkali metal salt is Li(FTA), K(FTA) or Na(FSA), The organic polymer is one or more of polypropylene carbonate and polymethyl methacrylate.

4. The molten salt according to claim 1, characterized in that The alkali metal salt is a mixed salt of Li(FTA) / Li(FSA), a mixed salt of K(FTA) / K(FSA), or a mixed salt of Na(FTA) / Na(FSA). The glass transition temperature of the organic polymer exceeds 100°C.

5. The molten salt according to claim 4, characterized in that The organic polymer is one or more of polymethyl methacrylate and polyvinyl pyrrolidone.

6. A method for producing a molten salt, characterized in that: The method for producing the molten salt comprises: a dissolving step, in which an alkali metal salt and 5 mol % or more of one or more organic polymers having polar functional groups of N, O, or F coordinated to the cation of the alkali metal salt are dissolved in an organic solvent, wherein the alkali metal salt includes an anion having an amide structure or a methide structure, or an anion selected from BF4, PF6, ClO4, CF3SO3, C2F5SO3, C4F9SO3, and CF3CO2; and A decompression step in which the molten salt containing the organic solvent is decompressed to be in a supercooled state.

7. The method for producing a molten salt according to claim 6, wherein: The alkali metal salt is lithium amide salt, potassium amide salt or sodium amide salt, The organic polymer is one or more of polypropylene glycol, polyethylene glycol, polypropylene carbonate, polymethyl methacrylate, and polyvinyl pyrrolidone.

8. The method for producing a molten salt according to claim 6, wherein The alkali metal salt is Li(FTA), K(FTA) or Na(FSA), The organic polymer is one or more of polypropylene carbonate and polymethyl methacrylate.

9. The method for producing a molten salt according to claim 6, wherein: The alkali metal salt is a mixed salt of Li(FTA) / Li(FSA), a mixed salt of K(FTA) / K(FSA), or a mixed salt of Na(FTA) / Na(FSA). The glass transition temperature of the organic polymer is higher than the glass transition temperature of the alkali metal salt and is 100° C. or higher.

10. The method for producing a molten salt according to claim 6, wherein The organic polymer is one or more of polymethyl methacrylate and polyvinyl pyrrolidone.

11. The method for producing a molten salt according to claim 6, wherein The organic solvent is acetonitrile.

Citation Information

Patent Citations

  • Molten salt battery

    JP2013232327A

  • Lithium secondary battery using lithium molten salt for electrolyte

    JP2014165110A

  • Molten salt bath, precipitate, and process for producing metal precipitate

    WO2006057231A1